Can Identity Buffer Against the Detrimental Effects of Threat? The Case of the Qatar Blockade - Amin, Azzam; Van Assche, Jasper; Abdelrahman, Mohamed; McCashin, Darragh; Al-Adwan, Duaa; Hasan, Youssef (Frontiers in Psychology, 2022)
In 2017, the blockade of Qatar Gulf states caused a plethora of effects on the country. This paper sought to examine the resulting threat effects of this blockade in terms of lowered self-esteem and well-being, and the potential buffering effects of an overarching identity. Using self-report questionnaire data from Qatari secondary school students (N = 1,410), multiple moderated mediation models investigated the predictive effects of youngsters’ perceived threat, via self-esteem, on their well-being, and the mitigating roles herein of, respectively, national, Gulf region, and Arab identity. Perceived threat was indeed related to lower well-being via lower self-esteem, and this relationship was equally strong for those low and high in social identity. In terms of the three facets of identity, the overarching Gulf identity seems the most predictive, and it even (marginally significantly) buffers the negative relationship between threat and reduced self-esteem.